The Effect of Adding Thyroxine Hormone (T4) to Commercial Feed on The Growth Profile of Pompano (Trachinotus blochii, Lacapede) - Indarwati, Indarwati; Lumbessy, Salnida Yuniarti; Azhar, Fariq (Hasanuddin University, 2024)
The purpose of this study was to analyze the effect of adding commercial feed with various concentrations of the hormone thyroxine (T4) on the growth profile of star pomfret (T. Blochii, Lacapede). This research was conducted for 50 days at BPBL Sekotong. The method used is an experimental method with a completely randomized design (CRD) which includes 4 treatment levels and 3 replications. consisting of: P1: control (without thyroxine hormone), P2: thyroxine hormone 1 mg/kg feed, P3: thyroxine hormone 1.5 mg/kg feed, P4: thyroxine hormone 2 mg/kg feed. Parameters measured were absolute weight, absolute length, specific growth rate (SGR), feed efficiency (EP), feed conversion ratio (FCR), survival (SR) and water quality. Data were analyzed using variance (ANNOVA) and continued with Duncan's test. The addition of the concentration of thyroxone hormone (T4) in commercial feed can affect the growth of star pomfret but does not affect the value of feed utilization efficiency (EPP), feed conversion (FCR) and survival (SR). The addition of the concentration of thyroxine hormone (T4) 2 mg/kg in commercial feed is the best treatment in star pomfret culture, because it can provide an absolute weight of 7.69 g, an absolute length of 3.50 cm, and a specific growth rate of 2.28%/day.